C-telopeptide pyridinoline cross-links (ICTP) and periodontal pathogens associated with endosseous oral implants - Oringer, R J; Palys, M D; Iranmanesh, A; Fiorellini, J P; Haffajee, A D; Socransky, S S; Giannobile, W V (Clinical oral implants research, 1998)
Detection of periodontal or peri-implant sites exhibiting progressing disease or those at risk of deterioration has proven difficult. Pyridinoline cross-linked carboxyterminal telopeptide of type I collagen (ICTP), a marker specific for bone degradation found in gingival crevicular fluid (GCF), has been associated with both bone and attachment loss in periodontitis and may be useful for predicting disease activity. The aim of this cross-sectional study was to examine the relationship between ICTP levels and subgingival species around implants and teeth from 20 partially and 2 fully edentulous patients. GCF and plaque samples were collected from the mesiobuccal site of each implant and tooth. Radioimmunoassay techniques were utilized to determine GCF ICTP levels. Plaque samples were analyzed utilizing checkerboard DNA-DNA hybridization. Traditional clinical parameters were assessed. Seventy-one implants and 370 teeth from 22 subjects were examined. ICTP levels and subgingival plaque composition were not significantly different between implants and teeth. Implant sites colonized by Prevotella intermedia, Capnocytophaga gingivalis, Fusobacterium nucleatum ss vincentii, and Streptococcus gordonii exhibited odds ratios of 12.4, 9.3, 8.1, and 6.7, respectively of detecting ICTP. These results suggest a relationship between elevated ICTP levels at implant sites and some species associated with disease progression. Longitudinal studies are necessary to determine whether elevated ICTP levels may predict the development of peri-implant bone loss.